Patear el tablero: Juegos de damas crueles - Feldman, Hernán (Latin American Theatre Review, 2005)
Alejandro Tantanián’s Juegos de damas crueles is a provocative play in which the constant eruptions of variegated games attempt to map the narratives that inform our notion of origin, religion, fatherhood, family, gender, and nation. This study argues that the omnipresence of games in Tantanián’s play is far from incidental. In fact, these games and the unstable narratives they engender are the primary artillery that Tantanián deploys in order to combat the arbitrary premises of the foundational narratives that shape the world as we know it. Tantanián thus stages a ludic labyrinth that turns these influential narratives upside down, thereby empowering the subaltern and changing the rules of the big game of life. In the end, Tantanián insinuates that the ritualistic laws we live by are abreast with the capricious rules of "innocent" games to which we rarely give a second thought. (HF, in Spanish)